MODEL KEPEMIMPINAN PAULUS: SEBUAH STUDI EKSPOSISI SURAT FILEMON - David Susilo Pranoto (Manna Rafflesia, 2018)
An important part of human life is leadership. Without human leaders do not understand how to direct their responsibilities. In this article try to contribute about the leadership model of an apostle Paul. In this article we will describe the principle of leadership through the Apostle Paul's life experience. Expected through this writing is to add insight into Christians who are entrusted with leadership responsibilities. So it leads to leadership that glorifies God.